The Application of Trial as an Adult Concept in Indonesia: Justice for Victims in Juvenile Murder Cases - Christiansen, Nicholas; Bakhtiar, Handar Subhandi (Journal of Law, Politic and Humanities, 2025)
The increasing incidence of serious crimes committed by juveniles, particularly murder, raises concerns about the adequacy of Indonesia’s juvenile justice system, which emphasizes rehabilitation over retribution. In contrast, the United States applies the "trial as an adult" concept, allowing juveniles to be tried in adult courts under specific conditions. This study employs a normative legal method using statute and comparative approaches to examine the potential application of this concept in Indonesia. It compares Indonesia's child protection-oriented framework with the U.S. waiver of jurisdiction mechanism. The findings reveal a legal gap in Indonesia’s system for handling grave offenses by juveniles, which often fails to provide substantive justice for victims. Therefore, the study proposes a hybrid judicial model that balances child protection with victim justice by introducing a dual-track court system and proportional sentencing tailored to juvenile maturity and offense severity